Optimization of process condition for preparation of sapota bar using Refractance window drying method. Issue 3 (17th February 2020) - Jalgaonkar, Kirti; Mahawar, Manoj Kumar; Vishwakarma, Rajesh Kumar; Shivhare, Uma Shanker; Nambi, V. Eyarkai
Abstract: Refractance window (RW) drying is an emerging thin layer drying method in which drying of a food product takes place by heat transfer from hot water to a product through a plastic film. This study was conducted to prepare sapota bar using a batch type RW system. Response surface methodology (RSM) was used to optimize the process variables viz. water temperature (WT) (84.3, 87, 91, 95, and 97.7 °C), initial pulp thickness (PT) (3.3, 4, 5, 6, and 6.7 mm) and pectin concentration (PC) (0.3, 1, 2, 3, and 3.7%). Drying time (DT), ascorbic acid content (AA), color, hardness, cohesiveness, gumminess, and chewiness of the bar were considered as dependent variables. WT played important role followed by PC and PT. Hardness, cohesiveness, gumminess, and chewiness increased but DT, AA, and L* value decreased with increase in WT and PC. Increase in DT and AA and decrease in L* value was observed with increase in PT. Optimum conditions of sapota bar preparation were found at 91 °C WT, 5 mm PT, and 2% PC with a drying time of 146 min. The moisture content, AA, L* value, hardness, cohesiveness, gumminess, and chewiness were 16 ± 1 g H2 O/100 g sample, 10.7 mg/100 g, 25.7, 26.2 kgf, 0.21, 5.37 kgf, and 3.12 kgf, respectively. The study demonstrated that the RW drying can be effectively applied for preparation of qualitysapota bar in lesser duration than the conventional tray drying method.